HUMAN RESOURCE MANAGEMENT IN THE ERA OF TECHNOLOGICAL DISRUPTION: A NEW PARADIGM FOR ADAPTIVE ORGANIZATIONS - Silvia Iskandar; Fitrah Sari; Mirsal Mirsal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The rapid advancement of technology has significantly disrupted Human Resource Management (HRM) practices, presenting both opportunities and challenges for organizations. This study aims to explore the impact of technological disruption on HRM, focusing on the transformations in recruitment, training, and employee management. By employing a qualitative methodology, the research utilized case studies from organizations such as Telkom and Unilever, complemented by interviews with HR leaders to analyze how they have successfully adapted their HR practices to the digital age. The findings indicate that organizations that integrate AI-driven tools and digital learning platforms into their HR processes have enhanced recruitment efficiency, employee engagement, and performance management. However, challenges such as employee resistance, job displacement concerns, and the need for continuous upskilling were also identified. The study suggests that organizations should prioritize creating an adaptive work culture, support employee well-being, and provide reskilling opportunities to ensure that technology complements human capital. These findings have important implications for HR professionals seeking to navigate the digital transformation of HRM, providing a roadmap for balancing technological adoption with human-centric strategies in the workplace